ANALISIS GAYA BAHASA DALAM SIMBOLISME MATAHARI TERBENAM PADA NOVEL SUNSET BERSAMA ROSIE KARYA TERE LIYE - Agustin, Nadira; Rulfida, Yanah; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to analyze the style of language in the symbolism of the sunset in the novel Sunset Bersama Rosie by Tere Liye using a stylistic approach. This study uses a qualitative descriptive method with documentation techniques to identify quotations containing sunset symbolism. The results of the analysis show that the use of the style of language in the symbolism of the sunset in the novel Sunset Bersama Rosie by Tere Liye plays an important role in describing the emotional journey of the main characters, namely Rosie and Tegar, who face the process of loss, healing, and sincerity. Through the use of rich language such as metaphor, simile, personification, hyperbole, paradox, imagery, repetition, poetic diction, and contextual symbolism. Tere Liye not only uses the symbol of the sunset as a background element but also as a means to convey deep feelings of the heart. The sunset symbolizes sadness, hope, and acceptance, and shows that every ending provides space for a new, more peaceful beginning. Through the symbol of the sunset, the novel Sunset Bersama Rosie by Tere Liye invites readers to reflect on the cycle of life and the potential for resurrection that arises from every loss.